Morphology and anatomy in Heliconia angusta Vell. and H. velloziana L. Emygd. (Zingiberales: Heliconiaceae) from the Atlantic forest of southeastern Brazil - SIMÃO, DANIELA GUIMARÃES [UNESP]; SCATENA, VERA LUCIA [UNESP] (Sociedade Botânica de São Paulo, 2001)
Foram estudados os caracteres morfo-anatômicos das raízes, caules, folhas e escapos de Heliconia angusta e H. velloziana, provenientes de Mata Atlântica, no sudeste do Brasil. do ponto de vista morfológico, H. angusta e H. velloziana apresentam diferenças de: tamanho dos indivíduos, forma das lâminas foliares, número e forma das brácteas da inflorescência. Possuem caracteres anatômicos em comum, tais como: raízes com canais de ar no córtex; rizomas com feixes de fibras isolados, feixes vasculares colaterais e endoderme e periciclo unisseriados; folhas apresentando canais de ar, feixes vasculares colaterais formando arcos e células epidérmicas com paredes pouco espessadas; escapos com feixes vasculares colaterais e feixes de fibras no córtex. A distribuição dos feixes de fibras, encontrada nas folhas e nos escapos, difere em cada espécie, possuindo então um valor diagnóstico, H. velloziana apresenta feixes de fibras contínuos. Canais de ar nas raízes e folhas com mesofilo estreito são caracteres que provavelmente podem estar relacionados com o habitat úmido, do subosque de Mata Atlântica.

Morphological and anatomical features of roots, stems, leaves, and scapes were studied in Heliconia angusta and H. velloziana from the Atlantic forest in the southeastern of Brazil. Morphologically H. angusta and H. velloziana show differences in their sizes, blade shapes, number and shape of inflorescence bracts. on the other hand, they have common anatomical characteristics such as: roots with air-canals in the cortex; rhizomes with isolated fiber bundles, collateral vascular bundles, and uniseriate endodermis and pericycle; leaves presenting air-canals and collateral vascular bundles forming arcs, and thin-walled epidermal cells; scapes with collateral vascular and fiber bundles in the cortex. The distribution of the fiber bundles in the leaves and in the scapes was different for each species, having a taxonomical value, H. velloziana presenting continuous fiber bundles. Air-canals in roots and leaves with narrow mesophyll might be related to the moist understorey of the Atlantic forest habitats.
Morfologia e anatomia de Heliconia angusta Vell. and H. velloziana L. Emygd. (Zingiberales: Heliconiaceae) em Mata Atlântica, no sudeste do Brasil
Keywords: H. angusta; H. velloziana; morphology; anatomy; vegetative organs